SQC and Fuzzy FMEA Reveal Defect Priorities in Fairy Tale Book Printing: SQC dan Fuzzy FMEA Mengungkap Prioritas Cacat Pencetakan Buku Dongeng - Oktaviya, Ananta; Aryanny, Enny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Quality control is a critical requirement in the printing industry to ensure products conform to predetermined standards and maintain visual and functional quality. Specific Background PT XYZ, a large-scale printing company in Indonesia, records fairy tale books as the product with the highest defect rate across Web Printing, Sheetfed Printing, and Finishing processes. Knowledge Gap Existing quality control practices at the company are predominantly focused on final inspection, creating a gap between quality standards and actual process conditions, while empirical applications of integrated SQC and Fuzzy FMEA in the printing industry remain limited. Aims This study aims to analyze defect characteristics and determine priority causes of defects in fairy tale book production using Statistical Quality Control (SQC) and Fuzzy Failure Mode and Effect Analysis (Fuzzy FMEA). Results SQC analysis identified dominant defects, namely dirty paper appearance (21.3%), color mismatch (17.9%), fold mismatch (17.8%), varnish crack (15.4%), floy (15.3%), and staple reject (12.3%). Fuzzy FMEA results indicate that fold mismatch caused by unstable temperature and humidity conditions in the production environment has the highest risk priority with an FRPN value of 3.42, followed by operator inaccuracy, improper machine settings, inconsistent raw material quality, and weak supervision. Novelty This research presents an integrated application of SQC and Fuzzy FMEA specifically within fairy tale book printing operations. Implications The findings provide a structured basis for prioritizing corrective actions through environmental control, operator training, machine adjustment, and raw material inspection to reduce defect levels in printing processes. Highlights: Dirty paper appearance represents the largest proportion of defects in fairy tale book production. Fold mismatch associated with production environment conditions shows the highest risk priority. Integrated analytical methods enable systematic prioritization of defect causes in printing processes. Keywords: Defects, Fairy Tale Books, Fuzzy FMEA, Quality, Statistical Quality Control